STIMULASI PERMAINAN EDUKATIF UNTUK MENINGKATKAN KEDISIPLINAN ANAK USIA DINI - Ema Zati Baroroh; Nur Istiqomah; Suciah Ningsih; Luthfia Delisa Sakinah (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2026)
ABSTRACT Discipline is an essential aspect of early childhood character development; however, many children have not consistently demonstrated disciplined behavior in their daily activities. This study aimed to examine the tendency of improving early childhood discipline through educational game stimulation at Kelompok Bermain X Pontianak. The study employed a pre-experimental One-Shot Case Study design involving seven children aged 4–5 years, selected using a purposive sampling technique. Data were collected through a sticker-based reward system, structured observations, and teacher interviews, and were analyzed using descriptive quantitative and descriptive qualitative approaches. The intervention was conducted over two consecutive days and consisted of discipline education, interactive storytelling using hand puppets, and a modified snakes-and-ladders educational game. The findings indicated that the total number of stickers increased from 8 on the first day to 22 on the second day, representing a 175% increase. The findings also suggest that children demonstrated greater ability to follow instructions, wait for their turn, tidy up toys, and use the three magic words (